Feeling old: An ageless emotion. A proposal to interpret the experiences of changing social roles and identities - Paoletti, Matteo; Tomasello, Vincenza (Quaderni di Psicologia Clinica, 2023)
In this article we explore the elderly state through two intervention experiences, within two different contexts in which the authors are professionally involved, that of school and that of active employment policies. In the two cases the "elderly" are very different in age. In the first case the “elderly person” is 17 years old; in the second there is a 33-year-old and a 60-year-old man. In fact, the experience of feeling elderly is explored, regardless of chronological age. From this point of view, the elderly state is not necessarily and exclusively related to a linear conception of the psychophysical development of the individual. Here we consider, for the definition of the elderly state, the importance of the relationship between the individual, his contexts of belonging, the social representation within which a person becomes elderly. Problems concerning the desocialization experienced by clients of the clinical psychology intervention will be considered when one experiences a change in one’s social role, or because one moves towards an exclusion from social relationships within which one can share a third thing, as it has been conceptualized by Renzo Carli, or if he is out of it and tries to get back into it. The workplace will be considered in particular. In the case of the young it is the transition from school to the world of work, in the other case of unemployed people looking for a job relocation.